The strangeness of himself in the novels of Rewas Ahmad and Lutfiya Dlemi: The novels (Zhn) and (Alam al-Nisa' al-Wahidat) are example - Shilan Mohammed Rashid Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Alienation is a human phenomenon, not inherited, but rather a creation, with the human being’s knowledge of what is going on around him. It is acquired with age, because the social, cultural, political and educational conditions that surround the human being are the main reason for the exacerbation of the phenomenon on his personality. From this basis, the book was able with the passage of time to express this The term socio-psychological through literary characters, so we see in all societies writers who expressed this phenomenon with a clear expression, after a group of philosophers and psychologists analyzed the impact of the surrounding environment on the writings of the book. Ahmed, and the novel (The World of Lonely Women) by Lutfia Al-Dulaimi, especially since they are considered among the active writers in the field of the feminist movement, and are famous for being a defender of women’s rights, and for this reason this phenomenon was one of the most important axes in the plot of the novel by the two writers. The Kurdish and Iraqi women in general and the reality in which they live in a psychological and subjective alienation abroad, their causes and the colorization of the dialogue of the main characters in the novel (The Woman and the World of Lonely Women) and the most important points Which the book was able to convey to us from a true picture of the expatriate woman and her problems, especially the negative side of the patriarchal society and its impact on women, and the confinement of her role in raising children and serving him and treating her as a slave under his command. We hope that we have succeeded in this scientific research, to shed light on the most important feminist literary figures in Kurdish and Iraqi literature.